Enterprise Resource Planning (ERP) Support For Internal Control Effectiveness - Widyaningdyah, Agnes Utari; Ezra, Luandre (Universitas Muhammadiyah Malang)
EERP is a software package which already changed the way data is collected, disseminated, and used. ERP systems also have built-in control which in every transaction is supervised carefully. However, only a few findings in accounting empirical research reveal how the ERP systems support internal control effectiveness. In this paper, we investigate the effect of ERP systems on internal control effectiveness over financial statements. Using annual reports of listed firms in the Indonesia Stock Exchange and logistic regression technique, we find that firms with ERP reported fewer general internal control weaknesses than firms without ERP. Hence, ERP adoption and implementation in Indonesia’s firms cannot reduce internal control weaknesses, especially in a specific levels of financial statements because they have not fully utilized the ERP control features.